KAJIAN EFEKTIVITAS PENGGUNAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA WARULOR KECAMATAN PACIRAN TAHUN 2021-2023 - Agus Wahid Suyoto; Haryanto; Hendrix Irawan (Yayasan Baitul Hikmah al-Zain, 2025)
This study examines the impact of village funds on community empowerment in Warulor Village, Paciran District, using a descriptive quantitative approach. The results show that 65% of respondents acknowledge the benefits of village funds for the village, but only 60% perceive an increase in knowledge. Regarding community empowerment, 75% of respondents believe village funds help improve quality of life and economic conditions, although not yet optimal. Hypothesis testing through T-Test and F-Test reveals no significant impact, either partially or simultaneously, between village funds and community empowerment, indicating the need for improvement in their implementation.